Fundamental theories of piezotronics and piezo-phototronics. (May 2015) - Liu, Ying; Zhang, Yan; Yang, Qing; Niu, Simiao; Wang, Zhong Lin
Abstract: Wurtzite structured mateirals such as ZnO, GaN, InN and CdS simultaneously exhibit piezoelectric, semiconducting and photoexcitation properties. The piezotronic effect is to use the inner crystal potential generated by piezoelectric polarization charges for controlling/tuning the charge carrier transport characteristics in these materials. The piezo-phototronic effect is about the use of piezoelectric charges to tube the generation, transport, separation and/or recombination of charge carriers at p-n junction. This article reviews the fundamental theories of piezotronics and piezo-phototronics, forming their basis for electromechancial devices, sensors and energy sciences. Starting from the basic equations for piezoelectricity, semiconductor and photoexcitation, analytical equations for describing the strain-tuned device current were derived. Through analytical calculations and numerical simulations, it was confirmed that the piezoelectric polarization charges can act in the form of inner-crystal charges in the depletion region, resulting in a change in Schottky barrier height, depletion region shift and/or formation of a charge channel, which can be used effectively to enhance the efficiency of LED, solar cell and photon detectors. Graphical abstract: The three-way coupling among piezoelectricity, photo excitation and semiconductor properties features the piezotronics and piezo-phototronics effect. Highlights: This manuscript is the first review on the fundamental theories of piezotronics and piezo-phototronics. In this manuscript, previous studies are unified and summarized in a logical way, and the influence of piezoelectric polarization on device material interface is clearly pointed out as three mechanisms: changing the Schottky barrier height and depletion width; shifting depletion region and changing depletion width in p-n junction; helping form a charge channel near the p-n junction interface, which could trap/repel carriers. As a review of the theoretical work, the manuscript can not only serve as a guidance for future theory development, but also help researchers understand the working principles of piezotronics and piezo-phototronics, and provide guidance for future design of experiments to rule out other factors as well as optimize the utilization of piezotronics/piezo-phototronics effect.